2019
DOI: 10.1007/jhep10(2019)280
|View full text |Cite
|
Sign up to set email alerts
|

Strong cosmic censorship in Horndeski theory

Abstract: The strong cosmic censorship hypothesis has recently regained a lot of attention in charged and rotating black holes immersed in de Sitter space. Although the picture seems to be clearly leaning towards the validity of the hypothesis in Kerr-de Sitter geometries, Reissner-Nordström-de Sitter black holes appear to be serious counter-examples. Here, we perform another test to the hypothesis by using a scalar field perturbation non-minimally coupled to the Einstein tensor propagating on Reissner-Nordström-de Sitt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…It would be interesting to extent this work to the case the background black hole is charged and study the behaviour of QNMs in this background and in different asymptotic spacetimes. If the background metric is the Reissner-Nordström black hole in dS spacetime an interesting effect in Gravity theory and in its scalar-tensor extension, is the Strong Cosmic Censorship (SCC) effect [38,52]. It was found in [53] that there intervals of the masses and charges of the scalar field that we have violation or not of SCC.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to extent this work to the case the background black hole is charged and study the behaviour of QNMs in this background and in different asymptotic spacetimes. If the background metric is the Reissner-Nordström black hole in dS spacetime an interesting effect in Gravity theory and in its scalar-tensor extension, is the Strong Cosmic Censorship (SCC) effect [38,52]. It was found in [53] that there intervals of the masses and charges of the scalar field that we have violation or not of SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the Einstein gravity, it has been suggested that SCC is violated if β > 1/2 [14,63,64]. But in the modified gravity, we should reconsider the criteria [44]. According to the field equation ( 2), to judge the extendibility of the black hole solution beyond the Cauchy horizon, we need…”
Section: Strong Cosmic Censorship In the Near-extremal Kerr-sen-de Sitter Spacetimementioning
confidence: 99%
“…where is the Christoffel symbol and the expansion G μν ∼ 2 + ∂ are used, we need ∈ L 2 loc with L 2 loc the space consisting of square integrable functions locally in V [44,65,66]. For the part of the energy-momentum tensor, we have…”
Section: Strong Cosmic Censorship In the Near-extremal Kerr-sen-de Sitter Spacetimementioning
confidence: 99%
See 1 more Smart Citation
“…The central result arising out of these analyses is the realization that the strong cosmic censorship conjecture is violated in the near extremal regime for non-rotating black holes, while for rotating black holes, the violation can be avoided. For black holes in Born-Infeld-de Sitter and Horndeski theory, the strong cosmic censorship conjecture has also been recently studied in [24,25].…”
Section: Introductionmentioning
confidence: 99%